DIFFERENCES IN OCULAR SURFACE DISEASE INDEX SCORE IN PATIENTS BEFORE AND AFTER COMBINATION OF PHACOEMULSIFICATION AND TRABECULECTOMY. - Avri Panggabean; Riski Prihatningtias; Arief Wildan; Maharani Cahyono (Jurnal Kedokteran Diponegoro)
Abstract